사용자의 스트레스 완화를 위한 맞춤형 콘텐츠 서비스 시스템의 설계 및 구현 - 김진성(Jin-Sung Kim); 김승훈(Seung-Hoon Kim) (한국콘텐츠학회 논문지, 11(2), 2011)
As the society has become maturer, stress has emerged as a hot social issue. In this paper, we proposed the design and implementation of a customized contents service system for relieving users' stress. In the proposed system, we compute the stress index from a user's biometics and psychology, and recommend a combination of video, sound, aroma, and lighting based on the index and user's data such as preferences, and provide the recommended contents service. We first classify symptoms of stress and then define a tool for self assessment. We classify video, sound, aroma, and lighting contents as well according to the defined symptoms. We propose 3-phase customized recommender and service model for customized contents service. We design and implement a customized contents service system for relieving users' stress. Different from existing systems, this proposed system has an individually-customized system and provides a diverse combination of different content's types. 사회가 점점 고도화 되면서 스트레스는 중요한 사회적 이슈로 부각되고 있다. 본 논문에서는 스트레스의 완화를 위한 맞춤형 콘텐츠 서비스 시스템을 설계하고 구현한다. 본 제안 시스템에서는 생체신호 및 심리정보를 기반으로 스트레스 증상 및 지수를 계산하고 선호도 등의 사용자 정보를 기반으로 영상, 음향, 향기 및 조명 콘텐츠 조합을 추천하고 추천된 콘텐츠 서비스를 제공한다. 이를 위하여 본 논문에서는 스트레스 증상을 분류하고, 심리정보 측정을 위한 자가평가도구 문항을 정의하였다. 정의된 스트레스 증상에 맞게 영상, 음향, 향기 및 조명 콘텐츠를 분류하였으며, 3단계 사용자 맞춤형 콘텐츠 추천 모델을 제안하였다. 또한 사용자 맞춤형 콘텐츠 서비스 모델을 제안하였으며, 이에 따라 서비스 시스템을 설계 및 구현하였다. 본 시스템은 기존의 시스템들과는 달리 사용자 맞춤형이며 다양한 콘텐츠 조합을 서비스할 수 있는 특징이 있다.